The development of the “Laab Nuer Model” for food safety management in handling traditional Lanna cuisine in Thailand - Vivat Keawdounglek; Supat Chaiyakul; Anuwat Aunkham (PLoS ONE, 2025)
Food contaminants in traditional Lanna cuisine persist as a public health issue since there is no readily apparent method to prevent this contamination. Hence, this study was conducted to develop a practical strategy for reducing food hazards in traditional Lanna cuisine, according to the farm-to-fork framework across upstream, midstream, and downstream operations. In the upstream operation, 80 sample analyses in a fresh market using the chemical test-kits were conducted, and 31 samples of produce were collected to analyze them for Paraquat contamination. In the midstream operation, a biological contamination analysis was conducted on 25 of the food handlers. In the downstream operation, which refers to the consumers, this study included a questionnaire to measure the level of agreement for the different factors by using the One Way ANOVA at the 0.05 level of significance. According to the “Laab Nuer Model” for traditional Lanna cuisine, one needs to consider the following at every stage:1) Uncontaminated market produce, including monitoring the raw material in the market, providing the activities linked to appropriate agricultural practices, and supporting the higher price if farmers adhere to good agricultural practices; 2) Good Restaurants including the monitoring of their raw materials, participating in food safety practices, and providing food safety training; 3) Paying Attention to the Consumer including training in food safety in the younger generation and promoting food safety. To significantly decrease the impact of foodborne illness in this and other locations, this model should be implemented widely, for example, in supermarkets and flea markets.